Jalaiah Effect: A Story of a Stolen Dance on TikTok and Trans-Platformization of Ignorance - Mariam Betlemidze (Social Media + Society)
This article explores how ignorance becomes a cultural affordance of trans-platformization, focusing on the Renegade dance’s evolution into a viral sensation that fueled TikTok’s rise and launched new teenage influencers. Employing new materialist feminist theory, Actor-Network Theory, and Critical Technocultural Discourse Analysis, this article operationalizes the concept of trans-platformization. It examines race-technology entanglements as they manifest during trans-platformization, highlighting the illusory progress in recognizing Black creators and the resistance against a predominantly White, techno-capitalist patriarchy. The tensions arising from these complexities intensify the demand for a more nuanced understanding of ignorance as the affordance of trans-platformization and the potential pivot point for speculative hope.